Airport marketing strategies : aviation and tourism perspectives - Florido-Benítez, Lázaro (Emerald Publishing Limited, 2024)
The perception of airports by tourists and business travellers alike, has dramatically improved over the last 25 years. This is partly due to the marketing strategies developed by airport operators, with the aim of establishing their place within the transportation, tourism, and logistics sectors. However, airports have not always been considered a cornerstone within these sectors. For decades, most tourists viewed airports as a simple, functional transport infrastructure, where they got on a plane to take a vacation, do business, or go home. Now, in the digital era, we see the travel sector, and airports especially, being revolutionised once again. Introducing students, researchers, and practitioners to the latest methods of airport marketing strategies in the digital innovation era, Airport Marketing Strategies: Aviation and Tourism Perspectives offers a contemporary global vision of airport marketing strategies in the context of the aviation and tourism sectors. These strategies increase commercial revenues, enhance promotion campaigns, boost the effectiveness of marketing actions, and promote an airport's brand image. Further, this book builds awareness and understanding of the various interactions and interdependencies between airports, Destination Marketing Organisations (DMOs), airlines, marketing tools, and stakeholders. The in-depth analysis is enhanced with real examples of airport marketing strategies from around the world.
Keywords: Airports -- Marketing.; Airports -- Technological innovations.; Strategic planning.; Business & Economics -- Marketing -- General.; Sales and marketing.; elektronické knihy; electronic books